Altered chromatin architecture and gene expression during polyploidization and domestication of soybean. Issue 5 (17th March 2021) - Wang, Longfei; Jia, Guanghong; Jiang, Xinyu; Cao, Shuai; Chen, Z Jeffrey; Song, Qingxin
Abstract: Polyploidy or whole-genome duplication (WGD) is widespread in plants and is a key driver of evolution and speciation, accompanied by rapid and dynamic changes in genomic structure and gene expression. The 3D structure of the genome is intricately linked to gene expression, but its role in transcription regulation following polyploidy and domestication remains unclear. Here, we generated high-resolution (∼2 kb) Hi-C maps for cultivated soybean ( Glycine max ), wild soybean ( Glycine soja ), and common bean ( Phaseolus vulgaris ). We found polyploidization in soybean may induce architecture changes of topologically associating domains and subsequent diploidization led to chromatin topology alteration around chromosome-rearrangement sites. Compared with single-copy and small-scale duplicated genes, WGD genes displayed more long-range chromosomal interactions and were coupled with higher levels of gene expression and chromatin accessibilities but void of DNA methylation. Interestingly, chromatin loop reorganization was involved in expression divergence of the genes during soybean domestication. Genes with chromatin loops were under stronger artificial selection than genes without loops. These findings provide insights into the roles of dynamic chromatin structures on gene expression during polyploidization, diploidization, and domestication of soybean. Abstract : Reorganization of chromatin structure was involved in expression divergence during polyploidization, diploidization, and domestication of soybean.